2017
DOI: 10.1161/circulationaha.116.023877
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Regulatory Effects of Myeloid Cell and Endothelial Cell NAPDH Oxidase 2 on Blood Pressure

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 42 publications
4
58
0
Order By: Relevance
“…In fact it was previously observed that endothelial dysfunction at least in response to angiotensin II is not observed in mice lacking monocytes [26] or deletion of monocytes [27] , [28] . Moreover, a striking similarity to the present data was observed in response to myeloid-specific deletion of Nox2; the animals had have lower blood pressure and increased NO levels [29] .…”
Section: Discussionsupporting
confidence: 88%
“…In fact it was previously observed that endothelial dysfunction at least in response to angiotensin II is not observed in mice lacking monocytes [26] or deletion of monocytes [27] , [28] . Moreover, a striking similarity to the present data was observed in response to myeloid-specific deletion of Nox2; the animals had have lower blood pressure and increased NO levels [29] .…”
Section: Discussionsupporting
confidence: 88%
“…Nox2 fl/fl mice were described recently (Sag et al, 2017) and were crossed with LysM-cre knock in mice (Jackson Laboratories 004781) to generate LysM-cre +/− Nox2 fl/fl and litter mate control Nox2 fl/fl mice . See supplemental methods for genotyping details.…”
Section: Methodsmentioning
confidence: 99%
“…In p47 phox -deficient mice, ANG II-induced hypertension (535) and afferent arteriolar contraction response are attenuated together with renal cortical NADPH oxidase activation (532). Nox2 deletion in ECs, but not in myeloid cells, attenuates ANG II-induced hypertension in mice (898). Thus, in EC-specific Nox2 transgenic mice, ANG II-induced endothelial dysfunction, hypertension, and cardiac remodeling are augmented (68,725,726).…”
Section: Ros Nox and Sodmentioning
confidence: 99%